Democratising access to dementia research - Ruth Dobson; Rimona Weil; Niran Rehill (Advances in Clinical Neuroscience & Rehabilitation, 2023)
As the UK population ages, dementia affects an increasing proportion of the population. There is a drive to accelerate dementia research, however access to research is not equitably distributed. We examine access to dementia research and discuss some enabling factors and barriers. High recruitment is frequently driven by a person (or people) dedicated to improving research participation. Barriers are commonly structural, rather than lack of willing or knowledge. A recurring issue was lack of time and/or resources. Leveraging existing infrastructure, such as streamlined and efficient governance frameworks, is a clear part of the solution. Research teams need to ensure inclusion/exclusion criteria serve the target population, and that any intervention is accessible to a range of patients. An injection of resources is crucial to support the recruitment process on the ground.